Discourse on Consumer Legal Protection on The Inclusion of Exoneration Clauses (Standardised Contract) In An Agreement - Tunggati, Melki T.; Ibrahim, Arif M.; Moha, Sri Wahyuni S. (Jurnal Hukum Bisnis, 2024)
The purpose of this study is to find out whether the standard agreement reflects the principle of freedom of contract in an agreement and the form of legal protection against the inclusion of the standard clause in an agreement. The results of this study indicate that the application of the standard clause in an agreement does not reflect and does not realize the principle of full freedom of contract, because the consumer has only the freedom to decide whether he makes a contract or not and the freedom to vote with whom he will make the agreement. While the debtor has absolutely no freedom to make agreements on the substance of the treaty, the contents of the agreement, the form of agreement and the manner of making the agreement and the protection of the law in the inclusion of the standard clause is set forth in article 18 of the consumer protection legislation regarding the ban on the inclusion of the standard clause. However, if in the implementation of the standard agreement there is a difference of interpretation of the standard contract formulation made by the parties then one of the legal efforts that can be done to become a defense fortress or legal protection to the consumer so that in the implementation of the standard agreement does not incriminate one party in contract, especially the consumer Then the standard contract formulation shall use the interpretation of an impartial agreement to the standard contractor.